Exploring the Role of Islamic Teachings in Ethical Leadership for Green Supply Chain Management : A Research Note - Dr. Mohammad Shahidul Islam; Md Shamimul Islam; Proma Quader (STIM LASHARAN JAYA MAKASSAR, 2023)
The relationship between Islamic teachings, ethical leadership, and green supply chain management (GSCM) practices is investigated in this research note. The Qur'an and Hadith guide the need for environmental protection, and incorporating religious wisdom into GSCM procedures can lead to sustainable and environmentally friendly supply chain management. The worldwide textile and leather industries, critical economic sectors in Bangladesh, have enormous potential for GSCM implementation. Incorporating Islamic teachings can play a vital role in supporting successful GSCM implementation. The paper offers managerial implications such as designing a tactical plan, using these lessons as training media, executing these concepts on a regular basis, and guaranteeing their communication and integration into daily operations. The paper continues by urging more research into combining religious understanding with GSCM practices for long-term success and prosperity.